Cultural Legitimacy, Electoral Pragmatism, and Digital Political Communication of the National Awakening Party - Prayitno, Dwi Agus; Purnomo, Agus (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
Studies on Islamic political parties in Indonesia have largely focused on ideological debates between Islam and democracy or descriptive analyses of electoral behaviour, leaving limited attention to the strategic transformation of cultural Islamic parties in contemporary electoral politics. This article examines the role of Partai Kebangkitan Bangsa (PKB) in Indonesian Islamic politics, asking three interrelated questions: how does PKB's cultural Islamic identity function as both a resource and a constraint in electoral competition? What mechanisms explain its transition from grassroots democratic education towards electoral pragmatism? Moreover, under what conditions does digital outreach reinforce rather than erode its traditional Nahdlatul Ulama (NU) base? Employing a critical narrative review of peer-reviewed journal articles, academic books, theses, and relevant political documents, this study synthesises scholarship from 1998 to 2024. The conceptual framework draws on Schwedler's inclusion-moderation thesis, Bayat's post-Islamism perspective, Pitkin's typology of representation, and Hefner's civil Islam framework. The findings reveal four interrelated patterns: PKB's cultural Islamic identity functions as a strategic resource that differentiates it within Indonesia's Islamic political spectrum; during the early Reformasi period (1999-2008) it served as an agent of grassroots democratic socialisation; from 2010 to 2020 a calculated shift towards electoral pragmatism unfolded; and the 2024 General Election demonstrated an adaptive integration of cultural legitimacy, policy-based representation, and digital outreach. The study contributes a theoretically grounded reconceptualisation of PKB as a culturally rooted yet strategically adaptive political actor, illustrating broader dynamics of moderation, identity negotiation, and democratic consolidation in contemporary Indonesian politics.